2016
DOI: 10.1128/iai.01227-15
|View full text |Cite
|
Sign up to set email alerts
|

The Effector Protein BPE005 from Brucella abortus Induces Collagen Deposition and Matrix Metalloproteinase 9 Downmodulation via Transforming Growth Factor β1 in Hepatic Stellate Cells

Abstract: The liver is frequently affected in patients with active brucellosis. In the present study, we identified a virulence factor involved in the modulation of hepatic stellate cell function and consequent fibrosis during Brucella abortus infection. This study assessed the role of BPE005 protein from B. abortus in the fibrotic phenotype induced on hepatic stellate cells during B. abortus infection in vitro and in vivo. We demonstrated that the fibrotic phenotype induced by B. abortus on hepatic stellate (LX-2) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Finally, to verify the in vivo significance of our hypothesis, Casp-1, ASC, NLRP3, and AIM2 KO mice and WT mice, as control, were infected with B. abortus, and 4 weeks later, animals were sacrificed to determine the role of inflammasome in the liver fibrosis. Accordingly with our previous results, Masson's trichrome staining revealed the presence of fibrotic patch in livers from B. abortus-infected mice with respect to uninfected control (9,15). In contrast, Casp-1, ASC, NLRP3, and AIM2 KO animals presented a significant reduction in the fibrotic patch (Figure 7).…”
Section: Nlrp3 and Aim2 Influence Liver Fibrosis In Livers From B Absupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, to verify the in vivo significance of our hypothesis, Casp-1, ASC, NLRP3, and AIM2 KO mice and WT mice, as control, were infected with B. abortus, and 4 weeks later, animals were sacrificed to determine the role of inflammasome in the liver fibrosis. Accordingly with our previous results, Masson's trichrome staining revealed the presence of fibrotic patch in livers from B. abortus-infected mice with respect to uninfected control (9,15). In contrast, Casp-1, ASC, NLRP3, and AIM2 KO animals presented a significant reduction in the fibrotic patch (Figure 7).…”
Section: Nlrp3 and Aim2 Influence Liver Fibrosis In Livers From B Absupporting
confidence: 89%
“…Previously, we have demonstrated that upon infection of HSCs, B. abortus triggers a profibrotic response characterized by inhibition of MMP-9 secretion inducing concomitant collagen deposition and transforming growth factor (TGF)-β1 secretion in a way that involves a functional T4SS and its effectors protein BPE005 (9). Taking into account that inflammasome has been documented to be necessary to induce activation to a fibrotic phenotype of HSCs, we hypothesized that Brucella infection might create a microenvironment that would promote inflammasome activation and concomitant profibrogenic phenotype in HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the functional aspects of proteases in Brucellae have not been investigated with proteomics so far. This is in sharp contrast to the proven importance of proteases for a great many functions such as host infection and persistence [89][90][91][92], stress response [92][93][94][95][96], morphology [97], communication and signaling [98][99][100], to name the most prominent.…”
Section: Proteases-a Yet Untouched Topic In Proteomics For Brucellamentioning
confidence: 84%
“…It has been demonstrated that autophagy participates in HSC activation (17). We have previously demonstrated that B. abortus infection induces HSC activation, leading to a profibrogenic phenotype (18,19). To determine if B. abortus infection induces the activation of the autophagic pathway in HSCs, we evaluated by Western blotting at 24 h postinfection the expression of LC3 II, the lipidated form of LC3 I, and the only known protein that specifically associates with autophagosomes (20), the autophagy regulator Beclin-1 (21), as well as p62, which participates in the autophagic clearance of ubiquitinated proteins (22).…”
Section: B Abortus Infection Induces Lc3-ii and Beclin-1 Expression mentioning
confidence: 98%